(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the application of artificial intelligence technologies in the field of taxation in the Republic of Uzbekistan. The main concepts of artificial intelligence, its role and capabilities in the taxation system are considered. In particular, attention is paid to the issues of automating tax processes, analyzing data, creating chatbots for taxpayers, and improving tax monitoring. At the same time, the legal status of artificial intelligence, its role in the taxation system, and the experience of developed countries are discussed. The results of the study indicate the prospects for introducing innovative technologies into the tax system of Uzbekistan.